Dinamika Sikap Tiongkok Atas Putusan Mahkamah Arbitrase Tetap Internasional Nomor 2013-19 dan Pengaruhnya terhadap Indonesia - Ayu Megawati; Gautama Budi Arundhati (Lentera Hukum, 2018)
The Conflict in South China Sea involves several countries in Southeast Asia, such as the Philippines, Vietnam, Malaysia, Brunei Darussalam, and Indonesia. It is dealt with the rights of ownership, as a result of the People Republic of China (PRC) to unveil nine-dashed line which partially claims over South China Sea. But, it is followed by other countries to release new evidences on the territorial status of South China Sea. Though the Permanent Court of Arbitration had decided the petition of the Philippines in 2013, PRC could not admit the Arbitration. Essentially, Indonesia is not directly involved as a party in the case. But as the evidence provided by PRC, Natuna Islands is part of nine-dashed line in which it asserts that such islands are regarded part of PRC. As a result, Indonesia needs to anticipate on the further potential contention of territorial claims as it has islands around the South China Sea.